Unravelling during cold storage and shelf life the pathological and physicochemical characteristics of postharvest apples and oranges - Allagui, Mohamed Bechir; Ben Amara, Mouna (Frontiers in Horticulture, 2025)
Fruits are susceptible to a diverse range of postharvest rots, which can reduce quality if preventive measures are not taken in time. In this study, samples of orange cv. Maltaise and apple cvs. Golden Delicious and Richared were sorted without infection or injury, treated or not with sodium metabisulfite (SMB), and then placed in cold storage for 20, 42, or 59–61 days, followed by a shelf life of 6 or 15 days. Physicochemical characteristics, degree of fruit infection, and weight loss were analyzed for each storage period. Our results indicated that adequate postharvest storage depends on the type of fruit, duration of cold storage, and shelf life. The heat map grouped ‘Richared’ apples close to its fresh state, without developing rot or perceptible weight loss for 60 days at low temperature (6°C) and 15 days of shelf life. These red apples performed better during storage than ‘Golden’ apples, especially in terms of storability and total flavonoids. Apples of ‘Golden’ showed better storage stability than ‘Maltaise,’ which could be stored properly for up to 20 days at 6°C, followed by a 15-day shelf life, regardless of treatment with sodium metabisulfite. The longer the oranges were stored, the greater the risk of infection and the greater the physicochemical properties; in this case, flavonoids decreased. The chemical criteria (TSS and pH) of apples and oranges were not affected by soaking in SMB, which was similar to that of untreated fruit. However, treating such fruits with SMB is regarded as unlikely because of its low effectiveness in preventing fruit decay during long-term storage. Cluster analysis showed that total polyphenols were linked to poor storability, whereas flavonoids, hardness, and TSS were associated with better storability. This suggests that flavonoids may be more reliable indicators of storage suitability than total polyphenols.